1990
DOI: 10.1152/ajpendo.1990.258.1.e126
|View full text |Cite
|
Sign up to set email alerts
|

Lipogenic enzyme activities and mRNA in rat adipose tissue at weaning

Abstract: The activities and mRNA concentrations of two lipogenic enzymes, fatty acid synthetase and acetyl-CoA carboxylase, and one enzyme involved in glyceroneogenesis, phosphoenolpyruvate carboxykinase (PEPCK), were measured in rat white adipose tissue during the suckling-weaning transition. Activities and mRNA concentrations of lipogenic enzymes were low in suckling rats, whereas activity and mRNA concentration of PEPCK were high. At weaning to a high-carbohydrate diet, the rapid increase in lipogenic enzymes mRNA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 28 publications
3
54
0
Order By: Relevance
“…The densitometric analysis of seven experiments revealed that 1 week after the VMH lesion the FAS mRNA expression was markedly increased (6-fold, p < 0.01) in WAT of VMH rats, in agreement with previous results [3]. PEPCK mRNA expression was markedly decreased (10-fold, p < 0.05) in WAT of VMH rats, in agreement with the well-known opposite regulation of FAS and PEPCK in WAT by modification of the hormonal and nutritional environment [22,26].…”
Section: Western Blotting Analysis Of Enzymes Involved In the Insulinsupporting
confidence: 91%
See 2 more Smart Citations
“…The densitometric analysis of seven experiments revealed that 1 week after the VMH lesion the FAS mRNA expression was markedly increased (6-fold, p < 0.01) in WAT of VMH rats, in agreement with previous results [3]. PEPCK mRNA expression was markedly decreased (10-fold, p < 0.05) in WAT of VMH rats, in agreement with the well-known opposite regulation of FAS and PEPCK in WAT by modification of the hormonal and nutritional environment [22,26].…”
Section: Western Blotting Analysis Of Enzymes Involved In the Insulinsupporting
confidence: 91%
“…These probes were labelled with [a-32 P] dCTP using a rediprime labelling system kit. Hybridization conditions were performed as described previously [21][22][23]. The blots were exposed for 6-48 h at − 80°C with intensifying screens.…”
Section: Map Kinase Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in adipose tissue, the increase in lipogenesis after weaning to a commercial diet (high carbohydrate) is accompanied by a large increase in three major lipogenic enzyme activities and levels of corresponding mRNAs (i.e. FAS, acetyl-CoA carboxylase, and ATP-citrate lyase (24,25)). Nuclear spot 14 protein, the expression of which matches that of lipid synthesis (26), is also induced by premature weaning and disappears in catabolic circumstances such as fasting (27).…”
Section: Discussionmentioning
confidence: 99%
“…Total cellular RNAs were extracted from cultured hepatocytes using the guanidine thiocyanate method [11] and prepared for Northern-blot hybridization as described previously [12]. Labelling of each DNA probe with [α-$#P]dCTP was performed by random priming (Rediprime labelling kit ; Amersham Pharmacia Biotech, Little Chalfont, Bucks., U.K).…”
Section: Isolation Of Total Rna and Northern-blot Hybridizationmentioning
confidence: 99%